Influence of manual thrombus aspiration on left ventricular diastolic function in patients with ST-segment elevation myocardial infarction treated with primary percutaneous coronary intervention - Ilić Ivan (Srpski Arhiv za Celokupno Lekarstvo, 2016)
Introduction. Data on effects of thrombus aspiration on left ventricular diastolic function in ST-elevation myocardial infarction (STEMI) population are scarce. Objective. We sought to compare echocardiographic indices of the diastolic function and outcomes in STEMI patients treated with and without manual thrombus aspiration, in an academic, high-volume percutaneous coronary intervention (PCI) center. Methods. A total of 433 consecutive patients who underwent primary PCI in 2011-2012 were enrolled in the study. Patients were not eligible for the study if they already suffered a myocardial infarction, had been previously revascularized, received thrombolytics, presented with cardiogenic shock, had significant valvular disease, atrial fibrillation or had previously implanted pacemaker. Comprehensive echocardiogram was performed within 48 hours. During follow-up patients’ status was assessed by an office visit or telephone interview. Results. Patients treated with thrombus aspiration (TA+, n=216) had similar baseline characteristics as those without thrombus aspiration (TA-, n=217). Groups had similar total ischemic time (319 ± 276 vs. 333±372 min; p=0.665), but TA+ group had higher maximum values of troponin I (39.5 ± 30.5 vs. 27.6 ± 26.9 ng/ml; p<0.001). The echocardiography revealed similar left ventricular volumes and systolic function, but TA+ group had significantly higher incidence of E/e’>15, as a marker of severe diastolic dysfunction (TA+ 23.1% vs. TA- 15.2%; p=0.050). During average follow-up of 14Ѓ}5 months, major adverse cardiac/ cerebral events occurred at the similar rate (log rank p=0.867). Conclusion. Thrombus aspiration is associated with a greater incidence of severe diastolic dysfunction in unselected STEMI patients treated with primary PCI, but it doesn’t influence the incidence of major adverse cardiovascular events. [Projekat Ministarstva nauke Republike Srbije, br. 175099]